When more is less : an analysis of the reforms in the system of direct taxation of profits from business activity in Uganda - Kwagala, Dorothy (2013)
Uganda is credited for carrying out extensive reforms in its tax system in the 1990s. The system of administration was overhauled together with a complete overhaul of tax legislation. The overriding objective was to increase tax revenues. Improvements were registered in the tax revenues but only temporarily. Since 2004, there has been stagnation in the tax revenue figures. The revenue from direct taxes only contributes about 20% to the total revenue well below the Sub-Saharan average of 40%. This has focused attention on the appropriateness of the reforms. The focus of the reforms on achieving efficiency did not sufficiently take into account the fundamental importance of equity within the system. As a result, the Income Tax Act 1997 embodies distortions and inequalities in the treatment of taxable income and taxpayers that have led to inefficiency in the system as a whole. The tax reforms also took a narrow technical view of the tax system. Taxation has an impact on state-building and is, therefore, affected by the state of governance. The reforms, even where they were well designed, have been affected by institutional weakness and the lack of accountability in the political process. The fact that institutional capacity affects effectiveness of the tax system is well documented yet it does not seem to have been taken into account in 1997 (UNDP, 1991:70). Taxpayer morale and revenues have been constrained by high levels of corruption within the Uganda Revenue Authority (URA) and arbitrariness in the award of tax waivers and other tax advantages. The purpose of the thesis is, therefore, to examine the distortions engendered by the tax system and their impact on taxpayer morale, tax revenue and investment. The thesis focuses on the direct taxation of profits from business activity in the formal and informal sector. An examination of the taxation of business profits provides an opportunity to highlight the distinctions in the tax system with regard to the treatment of the same type of income based on the legal status of the taxpayer and other considerations. The taxation of business profits in the corporate sector is compared with the taxation of business profits under the personal income tax system, taxation of partnerships and other unincorporated businesses. There is emphasis on the taxation of the informal sector which is presently less than satisfactory. However, the analysis is done in the context of the socio-political situation in Uganda. The weaknesses in governance and corruption have had an impact on the tax system by encouraging tax avoidance and evasion among political elites as well as on activities in the informal sector. The thesis also explores possibilities of broadening the tax base within the existing legislative framework as well as other possibilities for reform, for example, the call for the expansion of the tax base through taxation of land and agriculture by various experts and the URA itself (Private Sector Foundation- Uganda, 2009:122). Account must also be taken of Uganda’s membership of East African Community (EAC) and the constraints this puts on its exercise of fiscal sovereignty.